1988
DOI: 10.1164/ajrccm/138.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells from Rat Lung Are Potent Accessory Cells

Abstract: Accessory cells are required for the induction of lymphocyte proliferation in response to mitogens or antigens. Rat pulmonary cells were tested for the presence of accessory activity in lymphocyte proliferation induced by sodium periodate. Buffer-perfused lungs were excised, minced, and enzymatically digested. The resulting pulmonary cells (PC) were separated into high density (HD-PC, 32 to 57%) and low density (LD-PC, 9 to 32%) fractions in a discontinuous density gradient of bovine plasma albumin (BPA). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…This enhancement may be caused by induced in the function and the number of APC in the lung. Previous report show that DC isolated from parenchymal lung tissue exhibits strong AP activity (Holt et al, 1985;Rochester et al, 1988;Sertl et al, 1986). We assessed the AP activity of DC fraction in lung cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This enhancement may be caused by induced in the function and the number of APC in the lung. Previous report show that DC isolated from parenchymal lung tissue exhibits strong AP activity (Holt et al, 1985;Rochester et al, 1988;Sertl et al, 1986). We assessed the AP activity of DC fraction in lung cells.…”
Section: Discussionmentioning
confidence: 98%
“…Ia is expressed on dendritic cells (DC), macrophages, or B-cells, those play a role of APC in parenchymal lung tissue. DC isolated from parenchymal lung tissue exhibits strong AP activity in vitro (Holt et al, 1985;Rochester et al, 1988;Sertl et al, 1986). Inhalation of bacterial organisms recruits Ia positive DC into the airway epithelium (McWilliam et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Functional assays have included stimulation of periodate-treated lymphocytes, MLRs, and antigen-induced stimulation of either memory T cells or lymphoblasts. All have shown that lung DCs function as well or better than DCs from other sources Rochester et al, 1988;Pollard and Lipscomb, 1990).…”
Section: Lung Dendrite Cellsmentioning
confidence: 99%
“…Firstly, studies initially per formed in our laboratory [9] and confirmed by others [10,11] suggest that much of the APC activity detect able in suspensions derived from enzymatically dis rupted lung and airway tissue is attributable to a dendritic cell (DC)-like cell. Secondly, despite their seemingly sparse distribution in transverse sections of airways, significant numbers of la-positive cells can be detected in longitudinal frozen sections which pro vide a wider view of the airway epithelium [12][13][14], However, as is demonstrated below, appropriate sec tioning procedures reveal the presence of a much larger intra-epithelial la-positive cell population.…”
Section: Introductionmentioning
confidence: 96%